A retrospective study of indications and consequences of monitoring direct oral anticoagulant plasma concentrations on patient care in a university hospital: The Retro-AOD study. Issue 206 (October 2021) - Cavaillez, Thibaud; Weinmann, Laurent; Mouton, Christine; Delassasseigne, Céline; Sesay, Musa; Biais, Matthieu; James, Chloé; Roullet, Stéphanie
Abstract: Introduction: The use of direct oral anticoagulants (DOAC) is increasing. Specific concentrations are available and have been proven to be reliable and reproducible in optimising patient care. This retrospective, monocentric study aimed to describe the indications and consequences of monitoring DOAC plasma levels on patient care. Materials and methods: We collected data of patients hospitalised at the Bordeaux University Hospital between January 2017 and December 2018. These included demographics, indications, type, dose of DOAC, standard coagulation tests, creatinine clearance and DOAC plasma concentration using specifically calibrated rivaroxaban and apixaban anti-Xa and dabigatran anti-IIa assays. The date of last DOAC intake, the time between intake and plasma level measurement were also collected and analysed. Results: A total of 2197 DOAC assays in 1488 patients were obtained in various clinical situations: urgent or elective procedures, context of acute renal failure, suspicion or occurrence of ischemic strokes, intra-cranial and other bleeding sites. Interpretation of these assays led physicians to maintain, postpone or cancel invasive and high haemorrhagic risk procedures in 757, 261 and 56 cases respectively. The remaining 1123 assays were associated with no significant modification of patient care. DOAC plasma concentration was ≤30 ng ml -1 (sensitivity 85.4%, specificity 73.6%, positive predictive value 71.1%, negative predictive value 86.7%, AUC 0.81) after a last intake of at least 2 days. Conclusions: Our study is, to date, the largest report of real-life measurement of specific DOAC plasma level at a single institution. Patient care was not modified in more than half of the assays. Highlights: The use of direct oral anticoagulants (DOAC) is increasing. Specific assays are available, but little is known about their actual use in clinical routine. In a University Hospital 2197 assays were prescribed for over two years. Only 49% led to clinical decisions.